Pharmacological characterization of TQ05310, a potent inhibitor of isocitrate dehydrogenase 2 R140Q and R172K mutants. Issue 10 (20th August 2019) - Gao, Mingzhao; Zhu, Hongmei; Fu, Li; Li, Yun; Bao, Xubin; Fu, Haoyu; Quan, Haitian; Wang, Lei; Lou, Liguang
Abstract: Isocitrate dehydrogenase 2 (IDH2), an important mitochondrial metabolic enzyme involved in the tricarboxylic acid cycle, is mutated in a variety of cancers. AG‐221, an inhibitor primarily targeting the IDH2‐R140Q mutant, has shown remarkable clinical benefits in the treatment of relapsed or refractory acute myeloid leukemia patients. However, AG‐221 has weak inhibitory activity toward IDH2‐R172K, a mutant form of IDH2 with more severe clinical manifestations. Herein, we report TQ05310 as the first mutant IDH2 inhibitor that potently targets both IDH2‐R140Q and IDH2‐R172K mutants. TQ05310 inhibited mutant IDH2 enzymatic activity, suppressed (R)‐2‐hydroxyglutarate (2‐HG) production and induced differentiation in cells expressing IDH2‐R140Q and IDH2‐R172K, but not in cells expressing wild‐type IDH1/2 or mutant IDH1. TQ05310 bound to both IDH2‐R140Q and IDH2‐R172K, with Q316 being the critical residue mediating the binding of TQ05310 with IDH2‐R140Q, but not with IDH2‐R172K. TQ05310 also had favorable pharmacokinetic characteristics and profoundly inhibited 2‐HG production in a tumor xenografts model. The results of the current study establish a solid foundation for further clinical investigation of TQ05310, and provide new insight into the development of novel mutant IDH2 inhibitors. Abstract : Isocitrate dehydrogenase 2 (IDH2), an important metabolic enzyme, is mutated in a variety of cancers. AG‐221, the first‐in‐class IDH2 inhibitor, selectively inhibits the IDH2 mutant, IDH2‐R140Q, but shows weak inhibitory activity toward IDH2‐R172K. Herein, we report TQ05310 as the first mIDH2 inhibitor that potently targets both IDH2‐R140Q and IDH2‐R172K mutants.